Sir Christopher Hatton's Book of Seals : to which is appended a select list of the works of Frank Merry Stenton - Hatton, Christopher Hatton, Baron, 1605-1670 (Publications of the Northamptonshire Record Society, 1950)
Transcripts of 529 miscellaneous charters collected in full or partial facsimile in 1640 and ranging from the 12th to 17th century.